A case of ovarian hyperstimulation syndrome with spontaneous hemoperitoneum - Lele, Prasad R.; Tangri, Manoj Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
We report a case of complicated severe OHSS that developed spontaneous hemoperitoneum. This was a potentially fatal complication of pharmacological stimulation of ovary in assisted reproduction. Here the life was saved, oophorectomy was prevented and fertility preserved by timely diagnosis and conservative surgery.